Application of the fourth universal definition of myocardial infarction in clinical practice. (18th May 2020) - Mair, Johannes; Cullen, Louise; Giannitsis, Evangelos; Hammarsten, Ola; Huber, Kurt; Jaffe, Allan; Mills, Nicholas; Möckel, Martin; Müller, Christian; Thygesen, Kristian; Lindahl, Bertil
Abstract: Purpose: The Fourth Universal Definition of Myocardial Infarction (MI) has highlighted the different pathophysiological mechanisms that may lead to ischaemic and non-ischaemic myocardial injury and has emphasised that the diagnosis of myocardial infarction requires the presence of acute myocardial ischaemia in the setting of acute myocardial injury. This case based review intends to illustrate basic principles on how to apply this new, revised definition in clinical practice. Methods and Results: The distinction between different types of MIs (type 1 or type 2) and the delineation of MI from acute non-ischaemic myocardial injury may be challenging in individual patients, which is illustrated by presenting and discussing real-life routine cases. Conclusions: Type 1 MI is a consequence of coronary plaque rupture or erosion with intracoronary thrombus formation that is usually apparent on coronary angiography. Plausible triggering mechanisms causing myocardial oxygen supply/demand mismatch must be identified for the diagnosis of type 2 MI and its treatment should focus initially on management of the underlying disease attributable to acute myocardial ischaemia.